Effects of different exercise loads on serum betatrophin (ANGPTL-8/lipasin) and cartonectin (CTRP-3) levels in metabolic syndrome - Karaman, Muhammed Emre; Arslan, Cengiz; Gursu, Mehmet Ferit (Walter de Gruyter Gmbh, 2022)
Objectives The number of studies examining the circulating level change of betatrophin and cartonectin in metabolic syndrome applying different loads of exercise is limited. The purpose of the present study was to investigate how different loads of exercises regulate the betatrophin and cartonectin levels in metabolic syndrome induced rats. Methods A total of 24 Wistar-Albino male rats were used in the study. Rats were divided into four groups as follows; G1: control group (fed with standard diet and tap water), G2: metabolic syndrome group (without exercise application), G3: metabolic syndrome + aerobic exercise group (aerobic exercise applied), G4: metabolic syndrome + anaerobic exercise group (anaerobic exercise applied). Betatrophin and Cartonectin levels were determined by ELISA method in serum samples. Results There was a statistically significant difference in betatrophin levels between the groups and this differentiation was caused by G2 (p <0.05). Cartonectin levels were not significantly different between groups (p> 0.05). Conclusions It can be concluded that anaerobic exercises have more positive effects on glucose balance in metabolic syndrome than aerobic exercises, and by regulating betatrophin levels, anaerobic exercises indicate this effect.
Metabolik sendromda farklı egzersiz yüklenmelerinin serum betatrofin (Angptl-8/Lipasin) ve kartonektin (Ctrp-3) düzeylerine etkisi
Keywords: aerobic exercise; anaerobic exercise; betatrophin (ANGPL-8); cartonectin (CTRP-3); metabolic syndrome; aerobik egzersiz; anaerobik egzersiz; betatrofin (ANGPL-8); kartonektin (CTRP-3); metabolik sendrom